Effect of expertise on 3D force application during the starting block phase and subsequent steps in sprint running - Otsuka, M; Shim, J. K.; Kurihara, T.; Yoshioka, S.; Nokata, M.; Isaka, T. (Journal of Applied Biomechanics, 2014)
In sprinters with different levels of block acceleration, we investigated differences in their three-dimensional force application in terms of the magnitude, direction, and impulse of the ground reaction force (GRF) during the starting block phase and subsequent two steps. Twenty-nine participants were divided into three groups (well-trained, trained, and nontrained sprinters) based on their mean anteroposterior block acceleration and experience with a block start. The participants sprinted 10 m from a block start with maximum effort. Although the mean net resultant GRF magnitude did not differ between the well-trained and trained sprinters, the net sagittal GRF vector of the well-trained sprinters was leaned significantly further forward than that of the trained and nontrained sprinters during the starting block phase. In contrast, during the starting block phase and the subsequent steps, the transverse GRF vectors which cause the anteroposterior and mediolateral acceleration of the whole-body was directed toward the anterior direction more in the well-trained sprinters as compared with the other sprinters. Therefore, a more forward-leaning GRF vector and a greater anteroposterior GRF may particularly allow well-trained sprinters to generate a greater mean anteroposterior block acceleration than trained and nontrained sprinters.